Packaging Fatwa in the Post Truth Era: MUI Fatwa Contest Facing New Religious Authority - Zuhri, Achmad Muhibin; Wahyudi, Winarto Eka; Haeba, Ilham Dwitama (the Faculty of Ushuluddin, UIN Sunan Gunung Djati Bandung, 2023)
Indonesia has a federation organization that brings together several Islamic organizations. This organization is known as the Indonesian Ulema Council (MUI). One of his duties is to issue Islamic legal fatwas to serve as guidelines for the Muslim community. However, on a practical level, quite a few fatwas give rise to polemics. In several cases of intolerance and mobilization of political interests, MUI fatwas are often used as a means of legitimation. This article wants to discuss the contestation of the MUI fatwa with the dynamics of Islamic thought in Indonesia in the context of the digital era. Data was obtained from online news documents regarding MUI fatwas in several cases with social problems. This research found that the MUI fatwa polemic arose due to the need to consider Indonesia's social setting and political conditions. Hence, Islamic law products were prone to being misused and misunderstood. This study also argues that the MUI authorities must package the fatwa by prioritizing cultural diversity, social impacts, and political tensions at that time. Thus, the MUI fatwa must be formulated apart from being based on scientific grounds and supported by good online media infrastructure. So they will be better able to contest with the new religious authority in the post-truth era. Good fatwa packaging via social media is also oriented towards finding substantial values in responding to community problems based on the principle of uniting the community (tauhid al-ummah) and protecting the community (himayat al-ummah).